1986
DOI: 10.1139/y86-130
|View full text |Cite
|
Sign up to set email alerts
|

Is the change in intracellular pH during fatigue large enough to be the main cause of fatigue?

Abstract: The intracellular pH of frog sartorius muscles exposed to an extracellular pH 8.0 (25 mM HCO3-, 1% CO2) was 6.9-7.1. Following a fatiguing stimulation period (one tetanic contraction per second for 3 min), the intracellular pH was 6.5-6.7. When similar experiments were repeated with frog sartorius muscles exposed to pH 6.4 (2mM HCO3-, 1% CO2), the intracellular pH was 6.8-6.9 at rest and 6.3-6.4 following fatigue. So, in both experiments the intracellular pH decreased by 0.4-0.5 pH unit during fatigue. When th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

1989
1989
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 4 publications
3
31
1
Order By: Relevance
“…pHi values in unfatigued andfatigued sartorius muscles The pHi of unfatigued sartorius muscles from Rana pipiens is comparable to the pHi measured in semitendinosus muscles of the same species (Abercrombie, Putnam & Roos, 1983), and sartorius muscles of Rana temporaria (Curtin, 1986a). The decreases in pHi during fatigue development are similar to those obtained from muscle fibre type 1 of Xenopus laevis (Westerblad & Liinnergren, 1988), but they are 2 times greater than those obtained previously from frog sartorius muscles exposed to HC03- (Renaud et al 1986). This effect of buffer species on how pHi changes has also been reported in ischaemic ventricular muscles and Purkinje fibres (Vanheel, Leybaert, de Hemptine & Leusen, 1987;Bountra, Kaila & Vaughan-Jones, 1988).…”
Section: Effects On Pho and L-lactic Acid On Tetanic Force Recoverysupporting
confidence: 80%
See 1 more Smart Citation
“…pHi values in unfatigued andfatigued sartorius muscles The pHi of unfatigued sartorius muscles from Rana pipiens is comparable to the pHi measured in semitendinosus muscles of the same species (Abercrombie, Putnam & Roos, 1983), and sartorius muscles of Rana temporaria (Curtin, 1986a). The decreases in pHi during fatigue development are similar to those obtained from muscle fibre type 1 of Xenopus laevis (Westerblad & Liinnergren, 1988), but they are 2 times greater than those obtained previously from frog sartorius muscles exposed to HC03- (Renaud et al 1986). This effect of buffer species on how pHi changes has also been reported in ischaemic ventricular muscles and Purkinje fibres (Vanheel, Leybaert, de Hemptine & Leusen, 1987;Bountra, Kaila & Vaughan-Jones, 1988).…”
Section: Effects On Pho and L-lactic Acid On Tetanic Force Recoverysupporting
confidence: 80%
“…This is further supported by the following evidence. First, the net decrease in pHi observed at the end of a fatigue stimulus is too small to account for the change in force (Meyer, Kushmerick & Dillon, 1983;Renaud et al 1986). Second, muscle fatigue may occur without any change in pHi in patients suffering from McArdle disease (Shulman, 1980) or following strenuous but short bouts of exercise (V0llestad & Sejersted, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Some investigations point to a critical role for H+ accumulation (Sahlin, Edstr6m, Sjoholm & Hultman, 1981; and see Renaud, Allard & Mainwood, 1986), although work with metabolically inhibited muscles contradicts this (Parkinson, 1933;Edwards et al 1975). It has also been suggested that a combination of metabolite changes leading to a reduction in the free energy of ATP hydrolysis could be the cause of the slowing (Dawson et al 1980).…”
Section: Introductionmentioning
confidence: 99%
“…This is regularly observed in frog muscle preparations at the low temperatures generally used (e.g., Refs. 20,22,44). The reduced speed of force development is at least partly attributable to the change of the force-velocity relationship that occurs under these conditions leading to a lower speed of shortening at low and intermediate loads (15,22).…”
Section: Discussionmentioning
confidence: 99%
“…20; see also Ref. 44 for frog whole sartorius muscle), suggesting that the decrease in active force is mainly due to reduced force output of the individual cross bridges with little change in the actual number of attached bridges. Lowered intracellular pH also leads to a decrease in the maximum speed of shortening, as originally demonstrated by Edman and Mattiazzi (22) using the slack-test method (17).…”
mentioning
confidence: 96%